Improvement of iturin A production in Bacillus subtilis ZK0 by overexpression of the comA and sigA genes. (June 2017) - Zhang, Z.; Ding, Z.T.; Zhong, J.; Zhou, J.Y.; Shu, D.; Luo, D.; Yang, J.; Tan, H.
Abstract: Bacillus subtilis ZK0, which was isolated from cotton, produces a type of lipopeptide antibiotic iturin A that inhibits the growth of pathogenic fungi on agricultural crops. However, the low level of iturin A production by B. subtilis ZK0 does not support its large‐scale application. In this study, B. subtilis ZK0 was subjected to genetic manipulation to improve iturin A production. By the independent or simultaneous overexpression of two regulatory genes ( comA and sigA ), iturin A production by B. subtilis ZK0 was significantly increased. When both genes were simultaneously overexpressed under optimal conditions, iturin A production increased up to 215 mg l −1 (an approximate 43‐fold increase compared with B. subtilis ZK0). Moreover, overexpression of both genes was unexpectedly found to inhibit biofilm formation by B. subtilis ZK0, indicating that the phenomenon of 'stuck fermentation' would be avoided during B. subtilis ZK0 fermentation. In conclusion, a genetic manipulation method that improves iturin A production and inhibits biofilm formation in B. subtilis ZK0 is reported for the first time and this method has the potential to be widely applied in B. subtilis ZK0 commercial fermentation. Significance and Impact of the Study: This study provides new perspectives on improving iturin A production by Bacillus subtilis . Our newly engineered strains could be applied to commercial fermentation by enhancing yields of iturin A and reducing the rate of 'stuck fermentation'. Increased production would facilitate more widespread application of this powerful antibiotic. Abstract : Significance and Impact of the Study: This study provides new perspectives on improving iturin A production by Bacillus subtilis . Our newly engineered strains could be applied to commercial fermentation by enhancing yields of iturin A and reducing the rate of 'stuck fermentation'. Increased production would facilitate more widespread application of this powerful antibiotic.